CONSTRUCTION OF A EUKARYOTIC EXPRESSION VECTOR FOR PEGFP-FST AND ITS BIOLOGICAL ACTIVITY IN DUCK MYOBLASTS - PRO. MICHOULE SHINR, DR.DABPRY (International Journal of Multidisciplinary Research and Studies, 2021)
Follistatin (FST), a secreted glycoprotein, is intrinsically linked to muscle hypertrophy. To explore the function of duck FST in myoblast proliferation and differentiation, the pEGFP-FST eukaryotic expression vector was constructed and identified. The biological activities of this vector were analyzed by transfecting pEGFP-FST into cultured duck myoblasts using Lipofectamine™ 2000 and subsequently determining the mRNA expression profiles of FST and myostatin (MSTN). Results The duck pEGFP-FST vector was successfully constructed and was confirmed to possess high liposome-mediated transfection efficiency in duck myoblasts. Additionally, myoblasts transfected with pEGFP-FST had a better biological activity. Significantly, the overexpression of FST in these cells significantly inhibited the mRNA expression of MSTN (a target gene that’s negatively regulated by FST). Conclusions The duck pEGFP-FST vector has been constructed successfully and exhibits biological activity by promoting myoblast proliferation and differentiation in vitro.